Integrative Effects of Vinyasa Yoga and Animal Flow Exercises on Sprint Performance and Physiological Adaptations in Adolescent Male Sprinters - Paulraj, Victor A; Parasuraman, T (Physical Education Theory and Methodology, 2026)
Objectives. The aim of the study was to investigate whether the implementation of Vinyasa yoga or Animal Flow exercises alongside a structured sprint training programme would result in greater improvements in selected performance and physiological variables among adolescent male sprinters compared with a control group that performed sprint training only. Materials and Methods. Forty-five high-school male sprinters (16.0 ± 0.8 years) were randomly assigned to one of three conditions in a 12-week randomized intervention: sprint training only (ST), Vinyasa Yoga plus sprint training (VY+ST), or Animal Flow plus sprint training (AF+ST). All groups completed the same sprint training programme three times per week, while the experimental groups additionally performed 45 minutes of adjunct training on alternate days. Performance variables included 30-m sprint time, vertical jump height, and agility, whereas physiological variables included flexibility, estimated aerobic capacity (Cooper 12-minute run test), and resting heart rate. Pre- and post-test data were analysed using paired-samples t-tests and one-way ANOVA on change scores, with effect sizes reported. Results. Both integrative training groups demonstrated significantly greater improvements across all performance and physiological variables compared with the ST group (p < .05). The VY+ST group exhibited comparatively larger improvements in flexibility, estimated aerobic capacity, and resting heart rate, whereas the AF+ST group showed greater gains in vertical jump performance and agility. Large between-group effect sizes were observed for all outcome measures. Conclusions. The findings suggest that supplementing sprint training with Vinyasa Yoga or Animal Flow is associated with favourable and modality-specific adaptations in adolescent male sprinters. These integrative, movement-based approaches may serve as complementary strategies within youth sprint training programmes. However, given the indirect assessment of aerobic capacity and the absence of maturation control and a priori power analysis, the results should be interpreted with caution.